AKSES PENDIDIKAN DASAR: Kajian dari Segi Transisi SD ke SMP - Djoko Hartono (Jurnal Kependudukan Indonesia, 2008)
In Indonesia, despite the high rate of primary school enrolment that close to achieving the Universal Primary Education benchmarked at 100% in 2015, the enrolment at lower secondary education remains low. This is particularly the c E. mail: ase for the poor. Efforts to increase the transition from primary to junior secondary schooling is therefore important in order to increase the relatively low enrolment at basic education. Access to basic education service, primarily to school infrastructure is the main prerequisite in order to enable parents sending their kids to school. However, the availability of school building perse does not always guarantee parents will enrol their children to school. Findings from literature reviews suggest that apart from school building, there are other factors that predispose parents to take a decision whether or not to invest their household resources to education. These factors include direct and indirect costs of schooling, cultural and geographic distance to school, perceived benefits to schooling, et cetera. This paper will examines some major factors that relate to the decision making to enroll children to school through a descriptive analysis based on secondary data originated from BPS and Ministry of National Education, and blended with literature reviews. It is hoped that results of the analysis will be a valuable input in efforts to enhance the achievement of Nine Year Compulsory Basic Education Program that will come to an end in the 2008/09 school year.Keywords: Basic education, access to schooling, transition rate, compulsory education.